Financing Primary Health Care in Nigeria: A Case for Regional Reform, Targeted Subsidies, and Accountability (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Nigeria's healthcare system is a reflection of its economic situation. Health and wealth are intertwined. Good health improves productivity, strengthens household income, and contributes to national development and economic growth.1 However, in Nigeria, a country grappling with health issues such as malaria, tuberculosis, HIV/AIDS, and high maternal and child mortality, health remains more of a personal burden than a public right.2 These persistent health issues hamper health outcomes and economic development.